2018
DOI: 10.1088/1742-6596/957/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

High-Reflection Coatings for Gravitational-Wave Detectors:State of The Art and Future Developments

Abstract: Abstract. We report on the optical, mechanical and structural characterization of the sputtered coating materials of Advanced LIGO, Advanced Virgo and KAGRA gravitationalwaves detectors. We present the latest results of our research program aiming at decreasing coating thermal noise through doping, optimization of deposition parameters and postdeposition annealing. Finally, we propose sputtered Si 3N4 as a candidate material for the mirrors of future detectors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 12 publications
8
50
0
Order By: Relevance
“…This finding has possible interesting implications regarding a deeper comprehension of the mechanical behavior of these coatings for GWD purposes. Indeed, the finding regarding the Urbach tails parallels the well-known (yet still not fully understood) doping-induced reduction of internal friction observed in these films [7]. It has been shown that there is a correlation between mechanical losses and the disordered structure of this coatings [16,25].…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…This finding has possible interesting implications regarding a deeper comprehension of the mechanical behavior of these coatings for GWD purposes. Indeed, the finding regarding the Urbach tails parallels the well-known (yet still not fully understood) doping-induced reduction of internal friction observed in these films [7]. It has been shown that there is a correlation between mechanical losses and the disordered structure of this coatings [16,25].…”
Section: Resultssupporting
confidence: 73%
“…Regarding Ti:Ta 2 O 5 coating refractive index values, made at LMA, exploiting several Ti concentration were early presented in [12]. In that study Ti:Ta 2 O 5 coatings were deposited using various coating machines and variety of deposition methods, which provide films with different mechanical and optical properties [7]. In particular, the deposition conditions adopted to create the coatings analyzed in [12] were not the same used to deposit the materials currently used in GWD.…”
Section: Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the refractive index contrast by replacing the current co-sputtered Ta 2 O 5 -TiO 2 layers with higher-index materials, we tested Ta 2 O 5 -TiO 2 coatings with different Ti/Ta mixing ratios [31], Nb 2 O 5 layers and co-sputtered TiO 2 -Nb 2 O 5 coatings. Also, following preliminary results from the LIGO Collaboration, we tried Ta 2 O 5 -ZrO 2 coatings treated at higher annealing temperatures.…”
Section: Alternative Oxides and Dopingmentioning
confidence: 99%
“…Usually, such coatings are deposited by chemical vapor deposition (CVD), suffering from high optical absorption (k ∼ 1 − 5 · 10 −5 ) due to hydrogen contamination [34]; moreover, their thickness uniformity still remains to be tested against the stringent requirements of GW detectors. Thus we chose to develop our own IBS SiN x coatings and test their loss versus the annealing temperature [31]. The latest results are shown in Figs.…”
Section: Silicon Nitridementioning
confidence: 99%